Estimating Indirect Benefits: Fracking, Coal and Air Pollution - Reid Johnsen; Jacob LaRiviere; Hendrik Wolff (Institute for the Study of Labor (IZA), 2016)
This paper estimates indirect benefits of improved air quality induced by hydraulic fracturing, or "fracking". The recent increase in natural gas supply led to displacement of coal-fired electricity by cleaner natural gas-fired generation. Using detailed spatial panel data comprising the near universe of US power plants, we find that coal generation decreased by 28%. Further, fracking decreased local air pollution by an average of 4%. We show that benefits vary geographically; air pollution levels decreased by 35% in the most affected region. Back of the envelope calculations imply accumulated health benefits of roughly 17 billion annually.
Keywords: Q41; Q53; I18; 330; fracking; coal-fired power plants; air pollution; health; electricity